Novel anammox bacteria and nitrogen loss from Lake Superior. Issue 1 (December 2017) - Crowe, Sean; Treusch, Alexander; Forth, Michael; Li, Jiying; Magen, Cedric; Canfield, Donald; Thamdrup, Bo; Katsev, Sergei
Abstract Anaerobic ammonium oxidizing (anammox) bacteria own a central position in the global N-cycle, as they have the ability to oxidize NH4 + to N2 under anoxic conditions using NO2 − . They are responsible for up to 50% of all N2 released from marine ecosystems into the atmosphere and are thus indispensible for balancing the activity of N-fixing bacteria and completing the marine N-cycle. The contribution, diversity, and impact of anammox bacteria in freshwater ecosystems, however, is largely unknown, confounding assessments of their role in the global N-cycle. Here we report the activity and diversity of anammox bacteria in the world's largest freshwater lake—Lake Superior. We found that anammox performed by previously undiscovered bacteria is an important contributor to sediment N2 production. We observed striking differences in the anammox bacterial populations found at different locations within Lake Superior and those described from other locations. Our data thus reveal that novel anammox bacteria underpin N-loss from Lake Superior, and if more broadly distributed across inland waters would play an important role in continental N-cycling and mitigation of fixed nitrogen transfer from land to the sea.